2016
DOI: 10.1089/mdr.2015.0161
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Drug Resistance and Molecular Typing ofSalmonella entericaSerovar Rissen from Different Sources

Abstract: Salmonella enterica serovar Rissen is one of the most common serovars found in pigs and pork products in different countries, including Spain. However, information on the molecular bases of antimicrobial drug resistance and the population structure of Salmonella Rissen from different sources in Spain is limited. The present study focused on 84 isolates collected in Spain from pig and beef carcasses, foods and clinical samples associated with sporadic cases of gastroenteritis, and one outbreak. The majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…The fact that the Azores archipelago is composed by nine small islands with livestock as one of the major economic resources reinforces this possibility. Another detected cluster containing a PT isolate and a Spanish isolate (cluster D) seems to suggest the existence of either a S. enterica serovar Rissen strain already circulating within the Iberian Peninsula, as a result of intensive trade of live pigs and pork between Portugal and Spain [17], or a discrete phenomenon, as only two cases were detected. Also, these isolates present the resistance genes sul1, dfrA12, and aadA2, mirroring what has been previously reported [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The fact that the Azores archipelago is composed by nine small islands with livestock as one of the major economic resources reinforces this possibility. Another detected cluster containing a PT isolate and a Spanish isolate (cluster D) seems to suggest the existence of either a S. enterica serovar Rissen strain already circulating within the Iberian Peninsula, as a result of intensive trade of live pigs and pork between Portugal and Spain [17], or a discrete phenomenon, as only two cases were detected. Also, these isolates present the resistance genes sul1, dfrA12, and aadA2, mirroring what has been previously reported [17].…”
Section: Discussionmentioning
confidence: 96%
“…In Portugal, only 31 cases of human salmonellosis caused by S. enterica serovar Rissen were identified in a 12-year period (2000-2012) [9]. However, this is one of the most commonly reported serovars in pigs and pork, in several European and Asian countries [10][11][12][13][14][15][16][17]. This serovar has also been isolated less frequently from other sources, namely, beef, chicken, and seafood [14,15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated the high frequency of resistance and multidrug‐resistance among S . Rissen isolates obtained from different sources and mainly from pigs (Garcia‐Fierro et al., ). Moreover, the authors described a successful clone of S .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors described a successful clone of S . Rissen that is circulating among humans, pigs and other sources in the Iberian Peninsula and in other countries (Garcia‐Fierro et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation